2011
DOI: 10.4161/viru.2.2.15270
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics identifies ferritin in the innate immune response ofC. elegans

Abstract: When encountering a pathogen, all organisms evoke a protective response by inducing defense mechanisms to help fight off the invader. The invertebrate model organism Caenorhabditis elegans has proven to be valuable for studies of the host response and the small nematode mounts a substantial transcriptional response to numerous pathogens. Here, we use global quantitative proteomics to profile the response to infection with E. coli strain LF82 isolated from patients suffering from Crohn's disease, an inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 55 publications
1
39
2
Order By: Relevance
“…Pseudomonas aeruginosa) [27]. At the protein level, a similar response was observed for Clec-63 and Clec-65 following incubation with pathogenic E. coli LF82 [36]. The gene of Clec-41, the protein of which was also found in higher abundance here, has been previously described to be transcriptionally induced as a reaction against P. aeruginosa [27].…”
Section: Differentially Abundant Protein Familiessupporting
confidence: 77%
See 1 more Smart Citation
“…Pseudomonas aeruginosa) [27]. At the protein level, a similar response was observed for Clec-63 and Clec-65 following incubation with pathogenic E. coli LF82 [36]. The gene of Clec-41, the protein of which was also found in higher abundance here, has been previously described to be transcriptionally induced as a reaction against P. aeruginosa [27].…”
Section: Differentially Abundant Protein Familiessupporting
confidence: 77%
“…In both cases, the effect of the pathogenic bacteria and the non-pathogenic Escherichia coli (OP50) on the host was studied independently. In another study, the interaction of C. elegans with the pathogenic E. coli strain LF82 in comparison to the E. coli food source strain OP50 was investigated using 14 N/ 15 N-metabolic labeling followed by GeLC-MS [36]. In the two biological situations, 117 proteins were identified at differential abundances.…”
Section: Introductionmentioning
confidence: 99%
“…3C-D) including genes that encode proteins with proposed or demonstrated antimicrobial activity, such as lysozymes, C-type lectins, antimicrobial peptides, and ferritin (Boehnisch et al, 2011; Hoeckendorf et al, 2012; Schulenburg et al, 2008; Simonsen et al, 2011; Tarr, 2012). We verified hlh-30- dependent induction of 14 genes in this group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, survival analysis was combined with the generation of transgenic C. elegans strains carrying a transcriptional clec gene reporter and the subsequent analysis of spatial as well as infection-induced expression patterns in vivo [51][52][53] . These studies demonstrated that most of the investigated clec genes are expressed in the intestine ( fig.…”
Section: Elegans Clec Genes Function In Pathogen Resistancementioning
confidence: 99%